Do Couples Bargain over Fertility? Evidence Based on Child Preference Data - Timo Hener (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2010)
Empirical literature has found evidence in favour of household bargaining models.In contrast to earlier tests that are limited to assignable private goods, we use childpreference data in order to extend the empirical evidence on household bargaining topublic household goods. In the empirical analysis, we exploit the different theoreticalpredictions for couples with heterogeneous and homogeneous preferences derivedfrom household models. Our results indicate that couples bargain over fertility.Furthermore, we find that the ability to commit to household resource allocationsdepends on the gender of the partner with higher preferences.
Keywords: D01; D13; J13; J18; 330; Fertility; child preferences; intra-household allocation; bargaining; limited commitment; Familienplanung; Verhalten; Offenbarte Präferenzen; Verhandlungstheorie; Haushaltseinkommen; Familienleistungsausgleich; Familienökonomik; Fruchtbarkeit; Theorie